Cotton Subsidies, the WTO, and the ‘Cotton Problem’ - Baffes, John (2012)
Following an 8-year long dispute over cotton subsidies, Brazil and the United States signed a Memorandum of Understanding on April 21, 2010, effectively paving the way for settling the dispute. This paper argues that cotton subsidies are just the tip of the iceberg while a number of other, perhaps more important, issues require attention and, indeed, political will. Chief among them is the persistent divergence between cotton prices and the prices of other agricultural commodities, which reflects, for the most part, the large supply response by China and India, a direct consequence of con-version to biotech cotton varieties in these (and other) countries. Such response -- which kept cotton prices low, compared with other commodities -- imposes a competitive disadvantage to non-users of biotech cotton. The paper also highlights two additional constraints faced by the cotton producing countries of West and Central Africa, namely, the structural inefficiencies of their primary processing industries (also known as ginning) and the appreciation of the CFA franc against the US dollar. Without downplaying the importance of subsidy elimination, the paper concludes that these impediments should receive high priority in the policy agenda.